2000
DOI: 10.3354/meps203161
|View full text |Cite
|
Sign up to set email alerts
|

Short-term and long-term effects of the toxic dinoflagellate Alexandrium minutum on the copepod Acartia clausi

Abstract: Several experiments were performed to determine the effects of cell toxin concentration, composition and toxicity of Alexandrium minutum on ingestion rate, egg production, hatching success and naupliar fitness of the copepod Acartia clausi. A combination of A. minutum and nontoxic algae (Prorocentrum micans, Tetraselmis suecica and Isochrysis galbana) was used as food. Copepods ingested a higher amount of A. minutum cells as the concentration of these toxic dinoflagellates increased, and also in response to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
50
2
7

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(68 citation statements)
references
References 30 publications
9
50
2
7
Order By: Relevance
“…Paralytic shellfish toxins are sodium-ion channel blockers that can cause potent neurotoxic syndromes in humans as well as fish, seabirds and marine mammals (Cembella, 1998;Turner and Tester, 1997;Turner, 2014). Reported effects on copepods offered PST-containing Alexandrium spp., however, range from none to adverse effects on ingestion rate, egg production, egg hatching and offspring development duration (Dutz, 1998;Frangopulos et al, 2000;Guisande et al, 2002). These variations in responses are not related to the overall toxicity of the cells (Teegarden et al, 2008) and raises the question of whether or not the PSP toxins actually function as a grazer deterrents.…”
Section: Introductionmentioning
confidence: 99%
“…Paralytic shellfish toxins are sodium-ion channel blockers that can cause potent neurotoxic syndromes in humans as well as fish, seabirds and marine mammals (Cembella, 1998;Turner and Tester, 1997;Turner, 2014). Reported effects on copepods offered PST-containing Alexandrium spp., however, range from none to adverse effects on ingestion rate, egg production, egg hatching and offspring development duration (Dutz, 1998;Frangopulos et al, 2000;Guisande et al, 2002). These variations in responses are not related to the overall toxicity of the cells (Teegarden et al, 2008) and raises the question of whether or not the PSP toxins actually function as a grazer deterrents.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional frameworks used to examine the grazer-toxic alga relationship, in which effects of the toxic alga are examined only on adult zooplankton (Teegarden and Cembella, 1996;Turner et al, 1998, Teegarden, 1999, Frango´pulos et al, 2000Colin and Dam, 2002a, b;Liu and Wang, 2002) have yielded disparate results partly because of uncertainty as to whether the individuals employed in the experiments came from resistant populations. Furthermore, such studies on adult stages alone are not sufficient to test for grazer resistance against toxic phytoplankton because population fitness was not measured.…”
Section: Introductionmentioning
confidence: 99%
“…De lo anterior, es factible pensar que a pesar de que N. scintillans se alimenta de G. catenatum, este dinoflagelado no fue un alimento adecuado durante las incubaciones. Frangópulos et al (2000) ha documentado que tanto la fecundidad como la producción de huevos por A. clausi fueron afectados cuando los adultos fueron alimentados con el dinoflagelado productor de toxinas paralizantes Alexandrium minimum por varios días. Estos autores también sugieren que el copépodo al alimentarse llega a un umbral que se autolimita por la asimilación de las toxinas.…”
Section: Discussionunclassified
“…It is plausible that, in spite of grazing activity by N. scintillans, G. catenatum is not a good food for this predator under the experimental conditions we used for several days. Frangópulos et al (2000) reported that fecundity and egg production of A. clausi were negatively affected when fed the tener un efecto en las tasas de pastoreo. La cepa utilizada en este trabajo es de las menos tóxicas de otras cepas aisladas de las costas mexicanas (promedio 13 pg STXeq célula -1 ), con un perfil dominado por las toxinas sulfocarbamoil tipo C (Band-Schmidt et al 2010).…”
Section: Interaccion De Noctiluca Scintillans Y Gymnodinium Catenatumunclassified